2016
DOI: 10.1186/s13550-016-0204-9
|View full text |Cite
|
Sign up to set email alerts
|

177Lu-OPS201 targeting somatostatin receptors: in vivo biodistribution and dosimetry in a pig model

Abstract: Background177Lu is used in peptide receptor radionuclide therapies for the treatment of neuroendocrine tumors. Based on the recent literature, SST2 antagonists are superior to agonists in tumor uptake. The compound OPS201 is the novel somatostatin antagonist showing the highest SST2 affinity. The aim of this study was to measure the in vivo biodistribution and dosimetry of 177Lu-OPS201 in five anesthetized Danish Landrace pigs as an appropriate substitute for humans to quantitatively assess the absorbed doses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 17 publications
1
29
0
Order By: Relevance
“…Two hundred micrograms are considered the upper limit for the agonist; however, there are indications that 200 mg might represent a starting dose for the antagonists. We understand the limitation of allometric scaling from mice to humans (5) and therefore agree with the authors that the benefit (safety and efficacy) of injecting larger amounts of antagonist peptide still needs to be investigated clinically. Animal experiments have been crucial in discovering the potential benefit of higher peptide mass, and these results should not be neglected because of hypotheses that have not been demonstrated.…”
Section: Replysupporting
confidence: 79%
See 1 more Smart Citation
“…Two hundred micrograms are considered the upper limit for the agonist; however, there are indications that 200 mg might represent a starting dose for the antagonists. We understand the limitation of allometric scaling from mice to humans (5) and therefore agree with the authors that the benefit (safety and efficacy) of injecting larger amounts of antagonist peptide still needs to be investigated clinically. Animal experiments have been crucial in discovering the potential benefit of higher peptide mass, and these results should not be neglected because of hypotheses that have not been demonstrated.…”
Section: Replysupporting
confidence: 79%
“…Also, in the human pilot study with 177 Lu-DOTA-JR11 (;150 mg peptide mass), the images recorded at 24 and 72 h showed low uptake in the pancreas and stomach, and the radiation dose to the pancreas and stomach wall were about 15 times lower than that to the kidneys (2). The biodistribution seems to be species-dependent: for example, differently from humans, pigs displayed a high uptake of 177 Lu-DOTA-JR11 in the osteogenic bone, but the spleen was not visible (5).…”
Section: Advantages and Limits Of Targeted Radionuclide Therapy With mentioning
confidence: 99%
“…Notably, up to 4.4 times higher tumor doses per injected activity were detected with OPS201 (1.8 ± 0.7 Gy/MBq vs. [ 177 Lu]-DOTATATE, 0.36 ± 0.07 Gy/MBq) 16, 47. Biodistribution in pigs also demonstrated encouraging results, which forecasts radiation exposure in humans in an acceptable range 48. A recently published abstract reported on 19 patients who underwent [ 68 Ga]-OPS202 imaging and subsequent [ 177 Lu]-OPS201 therapy (with 7/19 receiving two cycles): 1 patient achieved a complete response, 32% partial response and 47% remained stable.…”
Section: Potential Novel Radiotracers After Failure Of Conventional Prrtmentioning
confidence: 85%
“…In addition, sources of errors due to the allometric approach (relative to mass scaling) can be introduced because scaling most likely decreases the values of time-integrated activity curves, and consequently, the absorbed doses may decrease, as found by Beykan et al [30]. Moreover, Kranz et al [28] concluded that the extrapolation of preclinical data obtained from studies in small animals, either by organ harvesting or PET images, would result in an underestimation of the human effective dose due to limitations in allometric scaling and species-specific target expression; however, the current data provide a reasonable basis for evaluating human dosimetry, which can be better-established in human subjects.…”
Section: Discussionmentioning
confidence: 99%